Exploring how graft length shapes root system architecture and morphology in grapevine rootstocks - Mathieu Larrey; Jean-Pascal Tandonnet; Clément Saint Cast; Sarah Jane Cookson; Philippe Vivin (OENO One)
The success of grafting and the sustained growth of newly grafted grapevines depend on the ability of hardwood cuttings taken from parent plants to rapidly initiate new adventitious roots (ARs) and to establish a functional, well-distributed root system in the soil. There is a paucity of literature on the plasticity and diversity of grapevine root systems due to the difficulty of phenotyping the hidden part of the plant. This study aimed to investigate whether varying rootstock cutting length (8, 20, 30, and 50 cm), and as a consequence the initial pool of reserves, influences root system architecture (RSA) and root morphological traits of two scion/rootstock combinations, Vitis riparia cv. Riparia Gloire de Montpellier (RGM) and the V. berlandieri x V. rupestris hybrid cv. 1103 Paulsen (1103P), grafted with scions of V. vinifera cv. Cabernet-Sauvignon. Two experiments were carried out: one in 2022 involving 240 plants grown in pots, and another in 2023 with 32 plants grown in rhizotrons. The latter allowed for non-invasive, time-lapse 2D imaging of early root system development providing quantitative data on adventitious and lateral roots, including their number, length, diameter and branching patterns. The length of the rootstock significantly influenced the recovery and early-stage growth of the grafted grapevines, impacting both shoot and root development. Longer rootstocks led to accelerated emergence of ARs and increased their number, irrespective of rootstock genotype, as well as promoted greater total root system length and mass. The maximum number of ARs was positively correlated with graft fresh mass, suggesting a link between initial reserves and root development. While CS/1103P produced more ARs and had longer first-order roots compared to CS/RGM, both combinations produced similar total root biomass. However, they displayed distinct RSA patterns: 1103P ARs grew at narrower angles, while RGM roots spread more horizontally. These differences reflect varied strategies for soil exploration and resource utilization. Although certain root morphological traits remained unaffected by rootstock length, RGM showed greater plasticity in response to reduced initial reserves, as indicated by a smaller apical diameter with shorter grafts. Overall, this study emphasizes the significance of considering rootstock length and RSA in viticultural practices. The insights gathered here contribute to a deeper understanding of the mechanisms governing root development in grafted grapevines, thereby informing strategies to enhance grafting techniques and optimize grapevine cultivation.